REREADING THE ISSUE OF GENDER EQUALITY IN BAHTSUL MASAIL: AN ANALYSIS OF MAQASHID AL-SYARI’AH ON TRADITIONAL FIQH - Imam Syarbini; Kojin Kojin; Asmawi Asmawi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Gender equality issues in Islamic law remain a significant subject of debate amid social transformation and increasing demands for justice within contemporary Muslim societies. As a recognized forum for addressing emerging religious and social concerns, Bahtsul Masail plays a strategic role in formulating Islamic legal responses. However, the traditional fiqh approach that has long dominated its legal reasoning is often considered insufficient to comprehensively address the complexity of modern gender issues. This study aims to re-examine gender equality discourse within Bahtsul Masail through the perspective of Maqashid al-Shari’ah and to explore the possibility of methodological transformation from a text-centered fiqh approach toward a maslahah-oriented framework. Employing a qualitative library research method, this study analyzes classical fiqh literature, Bahtsul Masail decisions, gender studies in Islam, and contemporary Maqashid al-Shari’ah theories. Data were analyzed using content analysis and critical-interpretive approaches. The findings reveal that the Maqashid al-Shari’ah framework provides a more responsive legal methodology capable of promoting justice, public welfare, and gender equality while maintaining fidelity to Islamic legal sources. This epistemological transformation strengthens the role of Bahtsul Masail as a form of collective ijtihad that remains adaptive to social change and relevant in addressing contemporary gender issues within Muslim communities.